Digital Assessment of Acquired Alexia and Agraphia: On the Relevance of Written Discourse - Jaecks, P; Jonas, Kristina (Frontiers in Communication)

Kognitive Kommunikationsstörungen: Wenn die Zusammenarbeit von Sprache und geistigen Fähigkeiten durch eine neurologische Erkrankung beeinträchtigt ist (2022. Aufl.) - Büttner-Kunert, J; Jonas, Kristina; Rosenkranz, A; Thöne-Otto, A

The Cologne Picture Naming Test for Language Mapping and Monitoring (CoNaT): An Open Set of 100 Black and White Object Drawings - Weiss Lucas, Carolin; Pieczewski, Julia; Kochs, Sophia; Nettekoven, Charlotte; Grefkes, Christian; Goldbrunner, Roland; Jonas, Kristina (Frontiers in Neurology)
Language assessment using a picture naming task crucially relies on the interpretation of the given verbal response by the rater. To avoid misinterpretations, a language-specific and linguistically controlled set of unambiguous, clearly identifiable and common object–word pairs is mandatory. We, here, set out to provide an open-source set of black and white object drawings, particularly suited for language mapping and monitoring, e.g., during awake brain tumour surgery or transcranial magnetic stimulation, in German language. A refined set of 100 black and white drawings was tested in two consecutive runs of randomised picture order and was analysed in respect of correct, prompt, and reliable object recognition and naming in a series of 132 healthy subjects between 18 and 84 years (median 25 years, 64% females) and a clinical pilot cohort of 10 brain tumour patients (median age 47 years, 80% males). The influence of important word- and subject-related factors on task performance and reliability was investigated. Overall, across both healthy subjects and patients, excellent correct object naming rates (97 vs. 96%) as well as high reliability coefficients (Goodman–Kruskal's gamma = 0.95 vs. 0.86) were found. However, the analysis of variance revealed a significant, overall negative effect of low word frequency ( p < 0.05) and high age ( p < 0.0001) on task performance whereas the effect of a low educational level was only evident for the subgroup of 72 or more years of age ( p < 0.05). Moreover, a small learning effect was observed across the two runs of the test ( p < 0.001). In summary, this study provides an overall robust and reliable picture naming tool, optimised for the clinical use to map and monitor language functions in patients. However, individual familiarisation before the clinical use remains advisable, especially for subjects that are comparatively prone to spontaneous picture naming errors such as older subjects of low educational level and patients with clinically apparent word finding difficulties.

Digitale Diagnostik: Innovative Wege für die Sprachtherapie - Jonas, Kristina; Jaecks, P (Spektrum Patholinguistik Band 14 Schwerpunktthema: Klick für Klick: Schritte in der digitalen Sprachtherapie)

Subkortikale Läsionen links und rechts –Auswirkungen auf Sprache und Kommunikation

Vorschlag eines ICF-Core-Sets für Kognitive Kommunikationsstörungen nach Schädel-Hirn-Trauma

Abstractband zur 20. Jahrestagung der Gesellschaft für Aphasieforschung und –behandlung

Status Quo – Diagnostik und Therapie der Fazialisparese in der sprachtherapeutischen Praxis - Gerhards, L; Werker, S.; Hembach, P.; Jonas, Kristina

Evidence for robust abstract syntactic representations in production before age three - Foltz, Anouschka; Knopf, Karolin; Jonas, Kristina; Jaecks, Petra; Stenneken, Prisca (First Language)
This study investigated whether we can find reliable comprehension-to-production syntactic priming effects in children aged 2;0 to 2;11 and how phonological working memory and sentence production skills relate to the syntactic priming process. A finding of reliable syntactic priming effects would provide strong evidence that children’s syntactic representations are abstracted over individual lexical items. To test children at this young age, they were primed with simple and early-acquired transitive (e.g., tickling (a) baby) and unergative intransitive (e.g., running) syntactic structures. Children aged 2;7 to 2;11, primed with alternating prime structures, revealed a reliable syntactic priming effect. In addition, phonological working memory (moderated by age) and sentence production skills positively affected transitive productions. Children aged 2;0 to 2;6, primed either with alternating or cumulative prime structures, showed no priming effect. Together, the data indicate that children have robust abstract syntactic representations for the tested structures before age three and that both phonological working memory and production skills relate to children’s syntactic priming behavior, albeit in different ways.

Kognitive Kommunikationsstörungen - Informationen für Betroffene, Angehörige und Sprachtherapeut*innen. dbs-Informationsbroschüre - Büttner-Kunert., J; Jonas, Kristina; Quinting, J; Rosenkranz, A

Cortical time course of language processing – an exploratory nTMS study - Weiss Lucas, c.; Nettekoven, c.; Jonas, Kristina; Lichtenstein, T.; Grefkes, C.; Goldbrunner, R.

Observer-independent language mapping using a semantic decision task - Weiß Lucas, Carolin; Nettekoven, Charlotte; Jonas, Kristina; Lichtenstein, Thorsten; Grefkes, Christian; Goldbrunner, Roland
Keywords: 610 Medical sciences; Medicine

Cortical Inhibition of Face and Jaw Muscle Activity and Discomfort Induced by Repetitive and Paired-Pulse TMS During an Overt Object Naming Task - Weiss Lucas, Carolin; Kallioniemi, Elisa; Neuschmelting, Volker; Nettekoven, Charlotte; Pieczewski, Julia; Jonas, Kristina; Goldbrunner, Roland; Karhu, Jari; Grefkes, Christian; Julkunen, Petro (Brain Topography)

Quality of life in adults with neurogenic speech-language-communication difficulties: A systematic review of existing measures - Neumann, Sandra; Quinting, Jana; Rosenkranz, Anna; de Beer, Carola; Jonas, Kristina; Stenneken, Prisca (Journal of Communication Disorders)

FV42 Test–retest reliability of high-frequency rTMS for language mapping - Nettekoven, c.; Pieczewski, J.; Neuschelting, V.; Jonas, Kristina; Grefkes, C.; Goldbrunner, R.; Lucas, C.W.

„Aus dem Rahmen gefallen?" Metaphern und Idiome zur Identifikation kognitiver Kommunikationsstörungen - Quinting, J; Jonas, Kristina; Stenneken, P; Hußmann, K (Forschung Sprache)

What do we measure when we assess communication-related quality of life in people with aphasia? - Quinting, Jana; Beer, Carola; Rosenkranz, Anna; Jonas, Kristina; Stenneken, Prisca; Neumann, Sandra (Aphasiology)

PB7. Comparison of three different fMRI paradigms for language mapping - Nettekoven, C.; Jonas, Kristina; Lichtenstein, T.; Grefkes, C.; Goldbrunner, R.; Lucas, C. Weiß (Clinical Neurophysiology)

PB 87. Comparison of three different fMRI paradigms for language mapping - Nettekoven, C; Jonas, Kristina; Lichtenstein, T; Grefkes, C; Goldbrunner, R; Weiss Lucas, C.

P13 Congruency between speech-related areas investigated by fMRI and three rTMS protocols with different frequencies